The Nexus of Water, Ecosystems, and Agriculture in Endorheic River Basins: A System Analysis Based on Integrated Ecohydrological Modeling. Issue 10 (11th October 2018) - Sun, Zan; Zheng, Yi; Li, Xi; Tian, Yong; Han, Feng; Zhong, Ye; Liu, Jie; Zheng, Chunmiao
Abstract: In arid and semiarid areas, the issues of water security, ecological security, and food security are tightly interlinked. Understanding the water‐ecosystem‐agriculture (WEA) nexus in such areas is critical to their sustainable development. This study presents a basin‐scale integrated ecohydrological model and a paradigm for analyzing the WEA nexus through physically based modeling. The integrated model is successfully applied to the Heihe River Basin (HRB), the second largest endorheic river basin in China. A system analysis of the WEA nexus in the HRB is performed using the validated model. The major findings are as follows. First, reducing the amount of irrigation water applied to the midstream of the HRB produces widely varying effects on the water balance of the basin. Second, a threshold of 11.5 × 10 8 m 3 /yr is found for the streamflow from the midstream region to the downstream region, beyond which the contribution of the streamflow to the recovery of vegetation is trivial in the short term. Third, the trade‐off among water conservation, ecosystem protection, and food production in the HRB is strong, and it is highly sensitive to the water management strategy employed. Evaporative water‐saving practices are more desirable than direct water‐saving regulation of irrigation water from the perspective of the WEA nexus. Overall, the results of the study provide insights into the allocation of water resources, ecosystem conservation, and agricultural development in the vast arid and semiarid areas of the world. Key Points: A basin‐scale integrated ecohydrological model is developed that tightly links the water, ecosystem, and agriculture sectors in arid areas A system analysis of the water‐ecosystem‐agriculture nexus in a typical endorheic river basin is performed using the integrated model Water‐saving irrigation has significant advantages over direct regulation of irrigation water in the context of the complex nexus